An over-view of robot assisted surgery curricula and the status of their validation. (January 2015) - Fisher, Rebecca A.; Dasgupta, Prokar; Mottrie, Alex; Volpe, Alessandro; Khan, Mohammed S.; Challacombe, Ben; Ahmed, Kamran
Abstract: Introduction : Robotic surgery is a rapidly expanding field. Thus far training for robotic techniques has been unstructured and the requirements are variable across various regions. Several projects are currently underway to develop a robotic surgery curriculum and are in various stages of validation. We aimed to outline the structures of available curricula, their process of development, validation status and current utilization.Methods : We undertook a literature review of papers including the MeSH terms "Robotics" and "Education". When we had an overview of curricula in development, we searched recent conference abstracts to gain up to date information.Results : The main curricula are the FRS, the FSRS, the Canadian BSTC and the ERUS initiative. They are in various stages of validation and offer a mixture of theoretical and practical training, using both physical and simulated models.Discussion : Whilst the FSRS is based on tasks on the RoSS virtual reality simulator, FRS and BSTC are designed for use on simulators and the robot itself. The ERUS curricula benefits from a combination of dry lab, wet lab and virtual reality components, which may allow skills to be more transferable to the OR as tasks are completed in several formats. Finally, the ERUS curricula includes the OR modular training programme as table assistant and console surgeon.Conclusion : Curricula are a crucial step in global standardisation of training and certification of surgeons for robotic surgical procedures. Many curricula are in early stages of development and more work is needed in development and validation of these programmes before training can be standardised. Highlights: Several projects are underway to create a curriculum for robotic surgery. We review the main projects currently under development and validation. The curricula propose a range of methods using several simulation models.